Qualitative Analysis of Partial 16S rRNA Amplicon of Mitochondrial Gene of Stingless Bees in Pesawaran - Priyambodo, Priyambodo; Rustiati, Elly Lestari; Pratiwi, Dian Neli; Susanto, Alvin Wiwiet; Imtitsal, Aulia; Fahrezi, Aditya; Febriansyah, Muhammad; Kusuma, Andriyani Wijaya; Srihanto, Eko Agus; Saswiyanti, Enny; Sidik, Mahfud; Sa'uddah, Lousanja D.; Lestari, Indah Ayu; Yani, Ani Andri; Ramadhan, Viki (Jurnal Biologi Tropis, 2023)
Pesawaran is one of the areas that has the potential to cultivate stingless bees as producers of honey and propolis. This study was aimed at qualitatively analysing partial amplicons of the 16S rRNA gene from individuals found at the research site. The research was performed from April to September 2023 in an explorative approach. Based on the exploration that has been done in Harapan Jaya Village, Way Ratai District, Pesawaran Regency, individual stingless bees were obtained from 5 different colonies. Individual samples of stingless bees were further extracted and amplified by commercial kits. Each individual from 5 different colonies has successfully obtained its DNA amplicons. Based on qualitative analysis using 1% agarose gel, the size of the partial gene ranged from 400bp to 500bp. This result is in accordance with the data contained in the genbank, where the 16S rRNA gene size is more than 500bp. Therefore, it has been concluded that the size of the partial amplicons of the 16S rRNA gene of individual stingless bees from the 5 colonies that were obtained is actually in range of the size of the 16S rRNA gene of stingless bees that have been recorded in the genbank.